2011
DOI: 10.1039/c0ja00230e
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic plasma diagnostics on a low-temperature plasma probe for ambient mass spectrometry

Abstract: Since the inception of ambient desorption/ionization mass spectrometry, plasma ionization sources have played an increasing role in molecular mass spectrometry. Although a variety of discharge designs and geometries, along with a range of applications, have been introduced, very little published work has focused on the characterization and fundamental examination of these discharges, especially on the desorption/ionization processes they employ. In the present work, a simple yet effective ambient desorption/io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
86
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 35 publications
6
86
2
Order By: Relevance
“…The data in Figure 2 compare the effect of helium gas flow rates on the formation of sulfinyl radical ions for the A chain of peptide 1. Clearly, higher intensity of sulfinyl radical ions were formed with a higher helium flow rate, presumably due to higher number densities of radicals produced from more intense plasma [60]. However, consecutive oxidation of peptide side chain or reactions of the sulfinyl radical ions became more competitive and the overall yield or purity of the sulfinyl radical ions could be adversely affected [59], as shown in Figure 2c.…”
Section: Formation Of Peptide Sulfinyl Radical Ions Radical Attack Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…The data in Figure 2 compare the effect of helium gas flow rates on the formation of sulfinyl radical ions for the A chain of peptide 1. Clearly, higher intensity of sulfinyl radical ions were formed with a higher helium flow rate, presumably due to higher number densities of radicals produced from more intense plasma [60]. However, consecutive oxidation of peptide side chain or reactions of the sulfinyl radical ions became more competitive and the overall yield or purity of the sulfinyl radical ions could be adversely affected [59], as shown in Figure 2c.…”
Section: Formation Of Peptide Sulfinyl Radical Ions Radical Attack Ofmentioning
confidence: 93%
“…Studies have shown that molecular species (OH, N 2 , N 2 + , NO, and NO 2 ) as well as atomic species (metastable He, H, and O) are abundant in an AP helium LTP [60,61]. For peptides having intra-chain disulfide bonds, one major product after the nanoESI plume interacting with LTP were ions corresponding to the addition of O and H to the intact peptide ([M + nH + OH] n•+ ) [58,59].…”
Section: Formation Of Peptide Sulfinyl Radical Ions Radical Attack Ofmentioning
confidence: 99%
“…The creation of M + ions via charge transfer in pure helium discharges has been attributed to charge transfer with species such as N 2 + , NO + , and O 2 + [6,25]. However, neither N 2 + nor O 2 + has been observed in great abundance in a pure argon discharge [8], and neither ion is in the mass range observable with our instrument. Within the range that we have observed (≈35 < m/z < 110), there are no changes in the background spectra that would account for the increase in sensitivity via charge transfer ionization with the addition of H 2 to the discharge.…”
Section: Changes To Analyte Ionization Mechanism Potential Causes Formentioning
confidence: 80%
“…Based on cost and availability, argon would seem to be a good alternative to helium. However, experiments with pure argon discharges have yielded sensitivities 10-100 times worse than those recorded with helium plasmas using the LTP [8]. There is good reason to think that adding hydrogen to argon could improve its performance as an ADI plasma gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation